Effects of dexmedetomidine on neurocognitive disturbance after elective non-cardiac surgery in senile patients: a systematic review and meta-analysis. Issue 5 (May 2021) - Bi, Xiaobo; Wei, Jingxia; Zhang, Xia
Objective: Senile patients often experience neurocognitive disturbance after non-cardiac surgery. Several clinical trials have investigated if the perioperative intravenous use of dexmedetomidine has a positive effect on the prevention of neurocognitive dysfunction, but the results have been inconsistent. We performed a meta-analysis to investigate the effects of dexmedetomidine on neurocognitive disturbance after elective non-cardiac surgery in senile patients. Methods: The PubMed, Cochrane Library, EMBASE and China National Knowledge Infrastructure databases were comprehensively searched for all randomized controlled trials published before 1 February 2020 that investigated the efficacy of dexmedetomidine in the prevention of postoperative delirium (POD) or postoperative cognitive dysfunction (POCD). Results: Sixteen studies involving 4376 patients were included in this meta-analysis. Compared with the control (i.e., saline), the perioperative intravenous use of dexmedetomidine significantly reduced the incidence of POD and POCD. However, patients in the dexmedetomidine group were more likely to develop bradycardia and hypotension during the administration of dexmedetomidine than patients in the control group. There were no differences between the two groups in the incidence of nausea and vomiting or mortality rate. Conclusion: Dexmedetomidine has a positive effect on the prevention of neurocognitive disturbance in senile patients after elective non-cardiac surgery.